POTENSI PENGEMBANGAN WISATA EDUKASI BERBASIS TRADISI BUDIDAYA TEMBAKAU DI DESA TLILIR TEMANGGUNG - Arrazaq, Naufal Raffi; Nggilu, Ariyanto; Tasnur, Irvan (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
Tlilir Village is one of the villages in Temanggung Regency, Central Java, which is known as the best tobacco producer in Indonesia. To maximize the utilization of their regional potential, the people of Tlilir Village began to initiate the development of educational tourism as a form of synergy between the agricultural sector, education and tourism. The purpose of this study is to analyze the potential of tobacco cultivation-based educational tourism destinations in Tlilir Village, the potential to support the development of educational tourism in Tlilir Village, and the concept of developing tobacco cultivation-based educational tourism in Tlilir Village. This research uses qualitative methods.  The results showed that the potential for the development of tobacco-based educational tourism destinations in Tlilir Village was supported by natural potential, cultural potential, and artificial potential. Natural potential in the form of the natural environment of Mount Sumbing. Cultural potential in the form of traditions related to tobacco cultivation. Artificial potential in the form of the pioneering tobacco museum and the holding of the 1st Tlilir Art & Culture Festival. The development of tobacco cultivation-based educational tourism in Tlilir Village can be developed with the carrying capacity in the form of accessibility, amenities, government policies, and community involvement.  The development of tobacco cultivation-based educational tourism in Tlilir Village is focused on educational tourism with the concept of learning tutorials and exploration.